The Albanians in the Balkans during World War II - Mariyana Stamova (Historijski pogledi, 2022)
After the end of the First World War, some countries in the Balkans remained dissatisfied with the status quo achieved with the Versailles system of peace treaties. The Albanian movement for territorial and ethnic Albania failed to fully realize - Kosovo and Metohija remained in the Royal Yugoslavia, established in 1918, which emerged from the First World War as a victorious state. The large Albanian population is a serious problem for the Kingdom of Yugoslavia. One of the culprits, according to some researchers, is Belgrade's own political circles in the interwar period. Nationally, culturally, economically and politically, the Albanians in this period are in the worst position of any other national minority in the royal Yugoslavia. Here are a few examples to support the above. In the period between the two world wars, the Albanian minority in Yugoslavia did not have a single school in their mother tongue, nor did it have a single cultural, educational or economic association. Dissatisfaction among Albanians from Kosovo and Metohija is growing with the policy of colonizing the Serb population from other parts of the country. This policy of repression against the Albanian population in Kosovo and Metohija provoked his numerous emigration to Albania. Much of the progressive emigration, in the person of Hassan Prishtina, Bedri Peyani, Ibrahim Gjakova and others, is extremely hostile to the Yugoslav state. This was cleverly used by the Albanian and Italian governments to break up Yugoslavia years later. In this regard, it is very important for Italian intelligence to engage Kosovo emigration in order to achieve full Italian control over Albania and weaken Yugoslavia's position in the south. With the impending new military confrontation on the international field, which would undoubtedly affect this region of Europe as well, Albanians see a real opportunity to achieve their national goals. Undoubtedly, the Albanian territory is also included in the geostrategic plans of the major countries for conducting military operations in the Balkans and implementing their further plans. In this regard, Italy's goal of making Albania a bridgehead in the Balkans for control of the Straits and the Middle East is to support the aspirations of Albanian nationalists after their long struggle to create a state that unites all Albanians. The status quo of the Balkans, reached by the Versailles system of peace treaties, was destroyed in the course of the Second World War. From all the Balkan states Albania was the first to experience the new order of Hitler and Mussolini and with their help accomplished its national program, precisely с the unification of the Albanian people and establishment of an Albanian identity in the Balkans. With the capitulation of Yugoslavia on April 7, 1941, a new territorial situation was created for the Axis forces and their satellite allies. The partition of Yugoslavia is one of the conditions for the realization of the „New Order“ in Southeast Europe. Convinced that the time was coming when, with the help of Italy and Germany, Kosovo and Metohija, western Macedonia, the eastern regions of Montenegro, etc. would enter Albania's borders, the Kosovo Committee with leading figures of Albanian nationalism, such as Bedri Pejani, Rexhep Mitrovica, Ibrahim Gjakova and Rexhep Krasniqi, have elevated political concepts for ethnic and territorial Albania familiar from the interwar period. In these years „Greater Albania” was a wartime creature, which did not get international recognition. The end of the war also put to rest the idea of a national unification of the Albanian people. The Albanian state again had its boundaries established after the end of the World War I; a large part of the Albanian population was left outside of these borders.